The Effect of the Effectiveness of the Rice Food Assistance Program in Improving Community Welfare by the Bekasi Post Office - Maulana, Yusup; Ardi, Yahya Mara (Pascal: Journal of Computer Science and Informatics, 2024)
The social assistance food program in Indonesia has undergone various changes, starting from the launch of the Beras Miskin (Raskin) program in 1998 to its transformation into the Beras Sejahtera (Rastra) program in 2018. This program aims to improve the welfare of low-income communities. The effectiveness of this program is evaluated based on its achievement of goals and its impact on the living standards of the community. This study aims to assess the effectiveness of the rice food assistance in improving the welfare of the community, distributed through the Bekasi Post Office. This study uses a quantitative method with a descriptive approach and simple linear regression. Data were obtained from a questionnaire survey of 100 respondents in 10 sub-districts in Bekasi. Validity and reliability tests of the questionnaire were conducted before the regression analysis to assess the relationship between the effectiveness of rice food assistance and community welfare. Simple linear regression analysis shows a significant effect between the effectiveness of the rice food assistance program and the improvement of community welfare. The ANOVA test resulted in an F-value of 5.804 with a significance level of 0.018 (<0.05), indicating that the regression model is valid for prediction. The correlation (R) of 0.236 and the coefficient of determination (R-square) of 0.56 indicate that 56% of the variation in community welfare is explained by the effectiveness of food assistance.